Mestizo pedagogies: An epistemic proposal for intercultural education in Colombia and Latin America - Ramos Guerrero, Jorge Orlando; Martínez Castro, Andrés Felipe; Mafla Ortega, Liliam (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2026)
Emergent pedagogies have opened the possibility for discussions on localized, community-based, and counter-hegemonic forms of knowledge to emerge. However, there is no integrative pedagogical theory that focuses on the dialogue between traditional and academic knowledge. Therefore, this reflection article discusses the significance of intercultural dialogue, intercultural education, and the intercultural curriculum in pedagogical processes within the Colombian and Latin American territories, which are characterized by their cultural richness and diversity. To this effect, a deep reflection is presented on the interrelationships between school, community, and knowledge from the perspective of mestizo pedagogies as a mediating device, around which multiple epistemologies, cultures, subjectivities, and cosmogonies converge in the context of Pasto, Nariño—which can be extrapolated to Colombia and Latin America. Thus, through an intercultural curriculum, school, pedagogy, and teachers contribute to epistemological justice by revitalizing and validating the knowledge of territories and communities and integrating it into academia. This process strengthens the cultural identity of students, teachers, and communities. In addition, it fosters a sense of belonging, identity, and respect for diversity, and it contributes to restoring the social fabric of communities, strengthening social cohesion, and achieving peace through education in diversity.